Reverse Phase High Performance Liquid Chromatographic Estimation of Ceftazidime in Pharmaceutical Formulations - Balamuralikrishna, K.; Mahendra, K.; Syama Sundar, B. (Asian Journal of Chemistry, 2011)
An accurate, precise and reproducible high performance liquid chromatographic method was developed for the estimation of ceftazidime (CFZ) in bulk drug and pharmaceutical formulations. In this method, Luna C18 column (250 mm × 4.6 mm; 5 μ) with mobile phase consisting of buffer (0.01M disodium hydrogen phosphate, pH was adjusted to 5.0):acetonitrile:water (50:25:25 v/v/v). The flow rate was 1.5 mL/min and the detection wavelength was 254 nm. The linearity was observed in the range of 50-150 μg/mL with a correlation coefficient of 0.9995. The proposed method was validated for its linearity, accuracy, precision and robustness. The proposed method is simple, rapid, accurate, precise and reproducible hence can be applied for routine quality control analysis of ceftazidime (CFZ) in capsule dosage forms.